Localization of abrupt change in the North Atlantic thermohaline circulation - Johnson, H; Marshall, D (2002)
Recent climate model experiments, as well as paleoclimate records, suggest that the meridional overturning circulation or "thermohaline circulation" in the Atlantic Ocean could change abruptly as a result of global warming, and that this could have a significant impact on European climate. We use a reduced-gravity model to investigate the response of the Atlantic overturning circulation to changes in forcing. We find that variability at decadal and higher frequencies is confined to a single hemisphere. This implies that (a) overturning variability resulting from high frequency changes in buoyancy forcing in the Labrador and Greenland Seas will be limited to the North Atlantic, and (b) any observed decadal and higher frequency fluctuations in North Atlantic overturning can only result from changes in the surface fluxes within the North Atlantic basin itself. These results suggest that Southern Ocean wind forcing is not important for North Atlantic overturning on decadal and shorter timescales.